Induction of Mitosis Delay and Apoptosis by CDDO-TFEA in Glioblastoma Multiforme - Tsai, Tai-Hsin; Lieu, Ann-Shung; Huang, Tzuu-Yuan; Kwan, Aij-Lie; Lin, Chih-Lung; Hsu, Yi-Chiang (Frontiers in Pharmacology, 2021)
Abstract Background Glioblastoma multiforme (GBM) is the vicious malignant brain tumor in adults. Despite advances multi-disciplinary treatment, GBM constinues to have a poor overall survival.CDDO-trifluoroethyl-amide, a trifluoroethylamidederivative of CDDO, is an Nrf2/ARE pathway activator. CDDO-TFEA is used to inhibit proliferation and induce differentiation and apoptosis in glioma cells. However, it not clear what effect it may have on tumorigenesis in GBM. Methods This in vitro study evaluated the effects of CDDO-TFEA on GBM cells. To do this, we treated GBM8401 cell lines with CDDO-TFEA and assessed apoptosis, cell cycle. DNA content and induction of apoptosis were analyzed by flow cytometry and protein expression by Western blot analysis. Results CDDO-TFEA significantly inhibited the proliferation induced cell apoptosis on GBM 8401 cell line. Typical plasma membrane undergoes structural changes that cause translocation of phosphatidylserine from the inside to outside. Due to cell external pressure cause mitochondrial membrane potential change lead to cell apoptosis. Caspase-3 active respond to apoptosis phenomenon, continuous progression of apoptosis.In addition, treatment with CDDO-TFEA led to an accumulation of G2/M-phase cells. An analysis of Cyclin B1, CDK1 and Cyclin B1/CDK1 complex association suggested that cell cycle progression seems also to be regulated by CDDO-TFEA. Therefore, CDDO-TFEA may not only induced cell cycle G2/M arrest, it may also exert apoptosis in established GBM cells. Conclusion CDDO-TFEA can inhibit proliferation, cell cycle progression and induce apoptosis in GBM cells in vitro, possibly though its inhibition of Cyclin B1, CDK1 expression, and Cyclin B1/CDK1 association.